2016
DOI: 10.1158/1078-0432.ccr-15-3101
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mutations and ALK Rearrangements Are Associated with Low Response Rates to PD-1 Pathway Blockade in Non–Small Cell Lung Cancer: A Retrospective Analysis

Abstract: Purpose PD-1 inhibitors are established agents in the management of non-small cell lung cancer (NSCLC); however, only a subset of patients derives clinical benefit. To determine the activity of PD-1/PD-L1 inhibitors within clinically-relevant molecular subgroups, we retrospectively evaluated response patterns among EGFR-mutant, ALK-positive, and EGFR wild-type/ALK-negative patients. Experimental Design We identified 58 patients treated with PD-1/PD-L1 inhibitors. Objective response rates (ORRs) were assessed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
865
7
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,043 publications
(920 citation statements)
references
References 29 publications
41
865
7
7
Order By: Relevance
“…Even if EGFR-mutated tumors are often associated with PDL1 overexpression (D'Incecco et al, 2015), the low rate of tumor infiltrate lymphocytes (TILs) suggests a very low immune-dependence of these tumors. Recently Gainor et al have found a concurrent PD-L1 overexpression and high rate of TILs in the tumor microenvironment of only 1/57 TKI-naive and 5/57 TKI-resistant patients with EGFR-mutated NSCLC (Gainor et al, 2016), confirming a lack of immunogenicity in the majority of such tumors. Even if PD-L1 expression levels changed in 16 patients evaluated after EGFR-TKI therapy, however not significant variations in both TILs and PDL1 expression have been found before and after TKI.…”
Section: Immunotherapymentioning
confidence: 95%
“…Even if EGFR-mutated tumors are often associated with PDL1 overexpression (D'Incecco et al, 2015), the low rate of tumor infiltrate lymphocytes (TILs) suggests a very low immune-dependence of these tumors. Recently Gainor et al have found a concurrent PD-L1 overexpression and high rate of TILs in the tumor microenvironment of only 1/57 TKI-naive and 5/57 TKI-resistant patients with EGFR-mutated NSCLC (Gainor et al, 2016), confirming a lack of immunogenicity in the majority of such tumors. Even if PD-L1 expression levels changed in 16 patients evaluated after EGFR-TKI therapy, however not significant variations in both TILs and PDL1 expression have been found before and after TKI.…”
Section: Immunotherapymentioning
confidence: 95%
“…For example, the use of epidermal growth factor receptor (EGFR) TKIs is standard of care in patients with EGFR-mutation-positive NSCLC [92][93][94], and studies suggest that this population may not derive benefit from immunotherapy versus EGFR TKIs [95] or chemotherapy [96]. Therefore, the clinical benefit from monotherapy with anti-PD-1/PD-L1 antibodies remains suboptimal in EGFR-mutation-positive NSCLC, and novel combination and therapeutic approaches are needed [96].…”
Section: Immunotherapeutics and Patient Selectionmentioning
confidence: 99%
“…Gainor et al conducted a retrospective review on EGFR -mutated and ALK -rearranged NSCLC patients treated with PD-1/PD-L1 inhibitors after progression on TKIs. Though their sample size was small, zero of six patients with ALK -rearranged NSCLC had an objective radiographic response to checkpoint inhibition [59]. They also assessed PD-L1 expression in ALK -rearranged NSCLC prior to crizotinib and at the time of crizotinib resistance.…”
Section: Post-alk Inhibitor Therapymentioning
confidence: 99%